2020
DOI: 10.2337/ds19-0019
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Therapeutic Inertia, and Patients’ Medication Experience

Abstract: Factors contributing to therapeutic inertia related to patients’ medication experiences include concerns about side effects and out-of-pocket costs, stigmatization for having diabetes, confusion about frequent changes in evidence-based guidelines, low health literacy, and social determinants of health. A variety of solutions to this multifactorial problem may be necessary, including integrating pharmacists into interprofessional care teams, using medication refill synchronization programs, maximizing time with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“… 10 Therefore, the basal insulin dose in conjunction with oral therapy is widely used to initiate insulin therapy, though, even when fasting hyperglycemia is under control, it is necessary to control post-prandial hyperglycemia to achieve target HbA1c levels. 18 According to a study by Bzowyckyj and Begert, 19 the factors that led to therapeutic inertia related to patients’ medication experiences such as the concerns about medication side effects and treatment costs, society-attached stigma, confusion about frequent changes in evidence-based guidelines, low health literacy, and social determinants of health. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Therefore, the basal insulin dose in conjunction with oral therapy is widely used to initiate insulin therapy, though, even when fasting hyperglycemia is under control, it is necessary to control post-prandial hyperglycemia to achieve target HbA1c levels. 18 According to a study by Bzowyckyj and Begert, 19 the factors that led to therapeutic inertia related to patients’ medication experiences such as the concerns about medication side effects and treatment costs, society-attached stigma, confusion about frequent changes in evidence-based guidelines, low health literacy, and social determinants of health. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Failure to act, either through proper screening according to guidelines or through a change in dose or the addition of an agent, when A1C is above goal has severe consequences for PWD (Table 1) and misunderstanding of treatment dosing regimens. 1,6 Fear of needles and injection-related anxiety also play a role. 1,3 PWD report that fear of self-monitoring of blood glucose, pain from injections, weight gain, anxiety over changing doses of insulin, and psychological resistance to insulin were barriers to insulin therapy.…”
Section: Reasons For Therapeutic Inertiamentioning
confidence: 99%
“…1,3 Additionally, not being able to follow dietary A multidisciplinary team approach may not only reduce the provider's burden but will also overcome therapeutic inertia related to HC systems. 3,6 Studies showed that adding HCP…”
Section: Reasons For Therapeutic Inertiamentioning
confidence: 99%
See 1 more Smart Citation